(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Experience shows that the use of computer and information technology in the study of border guard cadets of general technical disciplines increases the share of independent work and activation of cadets, has a positive effect on the formation of their technical thinking, and imagery of certain phenomena and processes in memory enriches the perception of educational material and its technical understanding. As practice has shown, this type of lesson as a practical lesson is a form of independent cadet activity. Performing a practical task, cadets actively operate with the acquired knowledge, skills and abilities, carry out search activities. The research was carried out on the example of conducting a practical lesson with border guards of specialty "Telecommunications and Radio engineering" using a graphical editor Microsoft Office Visio. The purpose of this lesson was to combine cadets’ graphic work on the construction of basic electrical radio products on the plane using computer technology and maintaining active cadet intervention in the process of creating basic electrical circuits directly on the personal computer screen. The use of computer and information technologies in teaching of border guard cadets of general technical disciplines opens the possibility of using a personal computer as a means of improving the educational process in higher military education and the formation of technical skills, promotes the development of technical thinking, professional imagination.